2009
DOI: 10.1007/s12192-009-0115-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hsp90 partners discovered using complementary proteomic approaches

Abstract: Hsp90 is an essential eukaryotic molecular chaperone that stabilizes a large set of client proteins, many of which are involved in various cellular signaling pathways. The current list of Hsp90 interactors comprises about 200 proteins and this number is growing steadily. In this paper, we report on the application of three complementary proteomic approaches directed towards identification of novel proteins that interact with Hsp90. These methods are coimmunoprecipitation, pull down with biotinylated geldanamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 41 publications
(51 reference statements)
2
44
0
Order By: Relevance
“…Later studies showed that Tomm34 is mainly localized in cytosol and functions as a component of the large chaperone complex, which shuttles proteins from ribosomes to mitochondria (14,16). Recently, Tomm34 has been identified as an Hsp70 and Hsp90 co-chaperone (16,22,23), and, in addition to HOP (12), Tomm34 can serve as a scaffold protein by binding both Hsp70 and Hsp90. Therefore, the presented work is focused on the analysis of complex formation between full-length Tomm34 and its individual domains with Hsp70 and Hsp90 to disclose the structural relations between these proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies showed that Tomm34 is mainly localized in cytosol and functions as a component of the large chaperone complex, which shuttles proteins from ribosomes to mitochondria (14,16). Recently, Tomm34 has been identified as an Hsp70 and Hsp90 co-chaperone (16,22,23), and, in addition to HOP (12), Tomm34 can serve as a scaffold protein by binding both Hsp70 and Hsp90. Therefore, the presented work is focused on the analysis of complex formation between full-length Tomm34 and its individual domains with Hsp70 and Hsp90 to disclose the structural relations between these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Chaperones-Tomm34 protein was described previously as an Hsp90-interacting protein (22,23). Recently, Faou et al (16) reported Tomm34 protein as a co-chaperone able to bind both Hsp70 and Hsp90 chaperones.…”
Section: Tomm34 Simultaneously Binds Hsp70 and Hsp90mentioning
confidence: 99%
“…and Geldanamycin-Several recent studies presented profiles of the human HSP90 interactome using immunopurifications and affinity capture with immobilized HSP90 (23,27). These studies effectively identified several new and novel HSP90 interactors; however, these experiments were not designed to identify interactions that are sensitive to HSP90 ligands.…”
Section: Hsp90 Interactome Is Dynamic With Respect To Nucleotidesmentioning
confidence: 99%
“…Several groups have recently reported proteomics studies of the HSP90 interactome; however, these studies were focused on documenting HSP90 interactions under single experimental conditions with isolated proteins or were not designed to study how the dynamic interactions of this chaperone complex are influenced by HSP90 ligands (21)(22)(23)(24)(25)(26)(27). To gain proteome-wide resolution on the effects of ligands on the HSP90 interactome, we affinity-purified human HSP90 complexes from HEK293T cells in the presence of excess ATP, ADP, or the HSP90 inhibitor geldanamycin and used LC-MS/MS and spectral counting to quantify the effects of these ligands on the constituents of the HSP90 interactome.…”
mentioning
confidence: 99%
“…It supports the folding and maturation of a multitude of client proteins 8 . Many of these clients are involved in cell cycle and regulation, which makes Hsp90 an interesting cancer drug target [9][10][11][12][13] .…”
mentioning
confidence: 99%